Boosting Employee Performance: The Roles of Motivation, Work Environment, Discipline, and Communication - Ainani, Nuril; Simon, Zainal Zawir (SAN Scientific, 2024)
The purpose of this research is to examine the influence of work motivation, work environment, work discipline and communication on the performance of PT United Tractors Cakung CGS Division Employees. This type of research is explanatory research. The sampling technique uses salted samples. Data was collected using a survey method using a questionnaire. The data analysis method used is multiple linear regression analysis. The research results show that (1) work motivation has a positive and significant effect on employee performance. (2) The work environment has a positive and significant effect on employee performance. (3) work discipline does not have a significant effect on employee performance. (4) communication has no significant effect on employee performance. (5) work motivation, work environment, work discipline, and communication simultaneously influence employee performance. The managerial implications that can be drawn from these findings are very important for effective human resource management. First, high work motivation can be increased by providing appropriate incentives and encouraging employees to achieve higher targets. Second, a conducive work environment can be created by arranging a comfortable and safe workspace, as well as ensuring good working relationships between employees.